Analysis of high school students' perceptions of tutors in the educational process - Elena N. Luzgina; Milena E. Ivanova (Развитие образования, 2023)
There is a growing need for high-quality education that prepares students for the complex challenges of the modern world. As a result, the use of tutoring services is becoming increasingly common in the education system. However, it is necessary to study the opinions of high school students about the role of tutors and the use of their services in the educational process to determine the effectiveness of this approach. The relevance of this research lies in determining high school students' perceptions of tutors' role in the educational process. High school students are a key group of tutoring service consumers, and their opinions about tutors' role in the educational process may influence decisions about using such services. In this study, a survey method was used. The survey questions addressed students' opinions about tutors' role in the educational process, as well as their personal experience with using tutoring services. The analysis of the data showed that high school students generally have positive attitudes towards tutors and consider them important helpers in the learning process. Most of the survey participants noted positive results from using tutoring services, such as improved academic performance and confidence in their knowledge. However, some drawbacks of using tutoring services were also identified, such as high cost, mismatch of the tutor's and student's knowledge levels, and insufficient effectiveness in some cases. The use of tutoring services can be an effective tool for improving academic performance and motivation among high school students, but the drawbacks and limitations of this approach should be taken into account. The results of this study can be useful for school administrations, parents, and high school students in making decisions about using tutoring services in the educational process.